Desa Wisata dan Prinsip Keberlanjutan: Studi Kasus: Negeri Oma, Kabupaten Maluku Tengah - Aletheia Deandra Siahaya; Wiendu Nuryanti (ATRIUM: Jurnal Arsitektur, 2023)
Title: Tourism Village and the Principles of Sustainability, Case Study: Negeri Oma, Central Moluccas Regency   The issue of sustainability becomes essential when a village or area is to be developed as a tourist destination because it has the potential to impact the life and environment of an area. Negeri Oma has been listed as one of the developing tourist villages in Central Mollucas Regency, according to the Ministry of Tourism and Creative Economy, since 2021. Some of its natural uniqueness are natural freshwater springs called Air Asol, natural hot springs, namely Air Panas Asol And Air Panas Bak, Pantai Sila, and the Tanjung Simale, scattered in the Negeri Oma Tourism Village area. The carrying capacity of tourism that has been owned is the availability of land and sea transportation, the availability of tourism and non-tourism supporting facilities, and the involvement of local communities. Research on tourism villages and sustainability principles uses descriptive research methods with a tourism architecture approach, in which data and information from the field are examined and supported by theories related to the research topic. The study results show that the development of the Negeri Oma Tourism Village has led to sustainable tourism. However, some deficiencies still require improvement and support from various parties so that tourism actors can continuously improve and enjoy the implementation principles.